Humanization of religious revelation when Hassan Hanafi - Sayeh Khan, Sarab; Saleh, Hussein (Al-Adab Journal, 2023)
The Egyptian thinker Hassan Hanafi was preoccupied with the concerns and problems of his time, the concerns and problems of the contemporary Arab reality. The question is the same, which is still being asked, why the Arabs were late and others advanced? In addition to the challenges imposed by the West on its lands, such as occupation, hegemony and wars, the need arose. Renewal of Arab thought to preserve the Arab-Islamic identity, the land...etc.; So, Hassan Hanafi turned to the sources of current Arab thought represented by the revelation (the Holy Qur’an) to come up with a new reading that serves human interests after previous interpretations neglected the problems of reality and were preoccupied with the divine essence and attributes. The revelation, in his opinion, is a speech from man to God, the searcher for the truth, to answer man’s questions and concerns, as stated in the reasons for revelation, and it is developing with the development of reality. As expressed in the abrogator and the abrogated, in addition to that, the independence of man in mind and will after the conclusion of the era of prophecy and revelation... so the mind became the heir of prophecy. Revelation was also considered a reference to the mind because it represents the experiences of past ages, so it can be achieved as a real system in the world.